Holly's story - McDaniel, Lurlene (New York : Delacorte Press, 2005)
With the support of her two best friends, high school senior Holly tries to deal with the murder of her brother and her anger at God for allowing the crime to happen.
Accelerated Reader AR
Keywords: Grief -- Juvenile fiction; Murder -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Friendship -- Juvenile fiction; High school seniors -- Juvenile fiction; Grief -- Fiction; Murder -- Fiction; Brothers and sisters -- Fiction; Friendship -- Fiction; High school seniors -- Fiction; Christian life -- Fiction; Florida -- Fiction; Christian fiction